Esophageal Perforation into the Pericardium in a 3-Year-Old Child with Esophageal Stricture: A Rare Complication Following Esophageal Dilatation - Nasser, Abdulrahman; Nassir, Raif; Awan, Muhammad Younas; AlShawa, Mohammad Anas; Habib, Zakaria (European Journal of Pediatric Surgery Reports, 2022)
Perforation of the esophagus during dilatation is a rare complication that might cause mortality. We present the report of a 3-year-old girl who was diagnosed with B cell acute lymphoblastic leukemia at 17 months of age. She experienced a complicated clinical course after chemotherapy was initiated, which included mucositis and acute pericarditis. She later developed an acquired esophageal stricture and tracheoesophageal fistula, which were managed with resection and primary anastomosis when she was in remission. Postoperatively, the patient developed a leak, which was treated conservatively. She subsequently developed a stricture that was treated successfully. On the fourth dilatation attempt and after she was sent home, she presented with persistent vomiting and low-grade fever and became vitally unstable on the same day, after stabilization, upper gastroenterology contrast revealed contrast filling the pericardium. She was managed conservatively with close observation and serial echocardiograms and then discharged home on day 18 in good condition after complete resolution of the pericardial effusion.
Keywords: esophageal dilatation; pneumomediastinum; pericardial perforation